Brief Report: Randomized, Double-Blind Comparison of Tenofovir Alafenamide (TAF) vs Tenofovir Disoproxil Fumarate (TDF), Each Coformulated With Elvitegravir, Cobicistat, and Emtricitabine (E/C/F) for Initial HIV-1 Treatment. (1st June 2017) - Arribas, José R.; Thompson, Melanie; Sax, Paul E.; Haas, Bernhard; McDonald, Cheryl; Wohl, David A.; DeJesus, Edwin; Clarke, Amanda E.; Guo, Susan; Wang, Hui; Callebaut, Christian; Plummer, Andrew; et al.
Abstract : Abstract: In 2 double-blind phase 3 trials, 1733 antiretroviral-naive adults were randomized to tenofovir alafenamide (TAF) or tenofovir disoproxil fumarate (TDF), each coformulated with elvitegravir/cobicistat/emtricitabine (E/C/F). At 144 weeks, TAF was superior to TDF in virologic efficacy, with 84.2% vs 80.0% having HIV-1 RNA <50 copies/mL (difference 4.2%; 95% confidence interval: 0.6% to 7.8%). TAF had less impact than TDF on bone mineral density and renal biomarkers. No participants on TAF had renal-related discontinuations vs 12 on TDF ( P < 0.001), with no cases of proximal tubulopathy for TAF vs 4 for TDF. There were greater increases in lipids with TAF vs TDF, with no difference in the total cholesterol to high-density lipoprotein ratio. For initial HIV therapy, E/C/F/TAF is superior to E/C/F/TDF in efficacy and bone and renal safety. Abstract : Supplemental Digital Content is Available in the Text.